Strengthening Farmer - Market Linkages - Paty, BK; Shalendra, S; Gummagolmath, KC (Journal of Agricultural Extension Management, 2018)
The Government of India has introduced reforms to promote development of the agricultural marketing sector by encouraging private participation, infrastructure creation and establishment of institutions supporting integrated supply chain. The measures may be slow, sporadic and scanty, but have helped in bringing desired change in the sector as reflected by the progress, made under direct marketing, contract farming and establishment of farmer consumer markets. The liberal environment of business and trade has led to the evolution of many institutions offering market access to small producers like cooperatives, farmers’ organizations and organized retail. The increasing use of ICT in agriculture marketing has the potential to propel the small farmers placed at the bottom of the pyramid upward by enhancing their income through better dissemination of information and their direct interaction with consumers. The states should come forward to implement the identified reforms, in letter and spirit, of the provisions laid down in the Model Act circulated by the central government to benefit the small and marginal farmers.